A Multi-Objective Dragongfly Optimization for Requirement Traceability Establishment - et. al., Swathine.K , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Software traceability is a crucial component of various exact software development process and it is needed for various component certification and approval process in security system. With the tremendous growth of system, traceability is considered as a recent research topic. The traceability is a software development process that is indefinable. Various manufacturers struggle in predicting the appropriate traceability degree for their needs and produce the appropriate set of traceability links. The effort, cost, and discipline have to be maintained with tracking links with the faster development of software systems that are extremely higher. Also, it produces various advantages in practical realization; as it can be either ad-hoc or not properly defined traceability process, produces poor training or lack of effectual tool support. Moreover, the traceability process has to be determined as it can diminish the development effort and to enhance the development process. Generally, traceability research is based on empirical investigations for exploring newer investigational queries or to compute newer tracing methods. Here, this work concentrates on traceability, functional requirements, link establishment. It shows a better trade-off among the prevailing approaches.